REALITA KEKUATAN EKONOMI ISLAM VERSUS KAPITAL DI EROPA DI ABAD 21 - Irsyamuddin, Dadang; Ghozali, Muhammad (Universitas Muhammadiyah Prof DR HAMKA, 2019)
Stretching the development of Islamic economics in the West is very massive in the 21st century. This is because Western societies have a more just economic system than the capital economy that they have implemented in recent years. and motivated by changes in the demographics of Muslim immigrants and the market needs of Muslims for halal lifestyle products that are in accordance with the call of Islam. But in the massive process, the West forgets a number of important points that are a big challenge today.